Web-Based GIS Housing Marketing Information System in West Papua - Saban, Ahmad Safitri; Marini, Ion Ferdinand; Aninam, Johny (International Journal Software Engineering and Computer Science (IJSECS), 2024)
Web GIS- Based Marketing Information System in Housing Sector of West Papua: A Case Study The methods of research are interviews, direct observation and documents sales report, regional maps). They note that the system offers a more direct and efficient means of accessing information from potential buyers, ultimately boosting marketing efficiency by as much as 45%. Moreover, it delivered a 30% higher sales conversion rate than traditional marketing channels. A combination of useful features such as interactive maps and location search functions helps potential buyers browse properties more easily, increasing the time they spend interacting with the platform and enhancing transaction chances. Many housing developers overcame challenges like the lack of internet backbone and a requirement for staff training to employ specialised skillsets. To needs, this research shows as an imperative using of Web gip to smooth the marketing and support strategic plan in housing construction. A recommendation for improving technological infrastructure and continuous training to ensure an effective utilization of the system is suggested. The results offer useful advice to housing developers looking to build innovative technology into their marketing strategy, thereby increasing efficiency and effectiveness within the housing sector.